Exploring Heart Leadership Model: a Case Study Among Leo Dehon Catholic Education Foundation in Indonesia - Wahyu Estining Rahayu, Caecilia; Edi Setiawan, Fransiskus (Journal of World Science, 2023)
Leadership models are crucial in managing Catholic education. It is imperative for leadership to possess specific models capable of resolving institutional or organizational issues. This research focuses on the heart-centered leadership model employed by the Chairperson of the Leo Dehon Indonesian Catholic Education Foundation. The study aims to explore this heart-centered leadership model and understand its dimensions within the Leo Dehon Catholic Education Foundation. Conducted using a qualitative research method with a descriptive single-case study design involving 11 staff members as research informants, the findings indicate the pivotal role of the Chairperson in driving positive change within the Leo Dehon Catholic Education Foundation. The Chairperson upholds noble values such as compassion, care, preparedness, sacrifice, optimism, and openness, all of which are reflected in the foundation's vision. Furthermore, the Chairperson sets an example through words, actions, and behaviors that embody sanctity, knowledge, and wholehearted dedication to service. This leadership example motivates self-development among members, staff, and employees. Moreover, the Chairperson reinforces organizational awareness by instilling a sense of ownership and responsibility towards the foundation. Consequently, this research implies that the leadership brought forth by the Chairperson has a significant impact on directing positive changes and fostering a resilient organizational culture. The leadership exemplified by the Chairperson influences the spirit and performance of individuals within the foundation, shaping a strong organizational identity based on upheld values.